A case report with COVID-19 during perioperative period of lobectomy. Issue 22 (29th May 2020) - Han, Peng; Li, Fan; Cao, Peng; Hu, Shan; Kong, Kangle; Deng, Yu; Zu, Yukun; Zhao, Bo
Abstract: Rationale: Currently, COVID-19 has made a significant impact on many countries in the world. However, there have been no reported cases of pulmonary lobectomy with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) infection. We are the first to report such a case. Patient concerns: We report a 63-year-old Wuhan male patient with smoking history of 40 cigarettes per day for 40 years. He sought medical consultation for right lower lung nodules found by CT scan. Diagnoses and interventions: The patient's postoperative pathological diagnosis was squamous cell carcinoma of the right lower lung. On the fourth day after the operation, the real-time reverse transcription polymerase chain reaction test showed a positive result. After the operation, we routinely give symptomatic treatments such as anti-infection, nebulization and oxygen inhalation. We also change antibiotics several times depending on the patient's condition. Outcomes: The patient's condition continued to deteriorate. On the fifth day after surgery, the patient died despite medical treatment. Lessons: We are the first to report the diagnosis and treatment process of patients with COVID-19 during perioperative period of lobectomy. It provides a case for the postoperative management of such patients.